(NmETODY NEWYPUKLOJ OPTIMIZACII (B/s - (NmIHALEWI^(B, (NwLADIMIR sERGEEWI^s; (NgUPAL(B, (NaNATOLIJ mIHAJLOWI^s; (NnORKIN(B, (NwLADIMIR iWANOWI^s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1987)
(NbIBLIOGR(B.: (NS(B. 273-279 (188 (NNAZW(B.)s
Keywords: (NmATEMATI^ESKAQ TEORIQs; (NoPTIMALXNYE PROCESSYs